Phenotypic Plasticity, Developmental Instability, and Robustness: The Concepts and How They Are Connected - Klingenberg, Christian Peter (Frontiers in Ecology and Evolution, 2019)
Developmental systems integrate inputs of variation from different origins into the observable variation of the resulting phenotype. Different components of phenotypic variation can be distinguished that correspond to those inputs, but the response of the system to each input factor can be modulated by other factors, so that there are interactions among the factors. This paper uses the concept of the target phenotype, introduced by Nijhout and Davidowitz to designate the expected phenotype for a given genotype and environment, to provide definitions and explanations of key concepts. This logic is put to use to explore the factors contributing to fluctuating asymmetry. To illustrate how genetic variation, phenotypic plasticity in response to temperature variation, and random developmental noise interact, this study uses computer simulations based on a simplified developmental model of a trait. The simulations show extensive interactions among the input factors, which can be explained by the non-linear nature of the developmental model. As a result, all the loci that control the developmental parameters end up affecting the resulting phenotypic trait, its reaction norm in response to temperature changes, and also its fluctuating asymmetry. Further, temperature (or possibly other environmental factors) can affect both trait values and the amount of fluctuating asymmetry without any involvement of stress. The model is broadly consistent with what is known from actual biological systems, and the results obtained from it have far-reaching implications for interpreting observations of the different types of phenotypic variation.